Controllable synthesis of Ni–Co–Mn multi-component metal oxides with various morphologies for high-performance flexible supercapacitors. Issue 39 (4th May 2017) - He, Pingge; Huang, Qun; Huang, Boyun; Chen, Tengfei
Abstract : Ni–Co–Mn multi-component metal oxides with various morphologies were controllably synthesized on carbon cloth for high-performance supercapacitor electrodes. Abstract : Ni–Co–Mn multi-component metal oxides with various morphologies for high-performance supercapacitor electrodes were controllably synthesized on carbon cloth through a facile hydrothermal method followed by a subsequent annealing process. The crystalline structure, morphology and electrochemical property of the metal oxides can be manipulated by simply adjusting the Ni/Co/Mn ratio in the solution. The metal oxide prepared in the solution containing a Ni/Co/Mn ratio of 1/1/2 presents a structure consisting of nanosheets and nanoneedles, and exhibits the highest specific capacitance of 1434.2 F g −1 at a current density of 2 mA cm −2, desirable rate capability and excellent cyclic stability with a capacitance retention of 94% over 3000 cycles. To demonstrate practical application, flexible asymmetric supercapacitors based on such metal oxides were prepared and show high capacitance, low internal resistance, excellent cyclic stability and outstanding flexibility, indicating great potential as high-performance energy storage devices.